Seletividade de inseticidas utilizados na cultura algodoeira a ovos e larvas de terceiro instar de Cycloneda sanguinea - Pedroso, E.c. [UNESP]; Carvalho, G.a.; Leite, M.i.s.; Rezende, D.t. [UNESP]; Moura, A.p. De (Instituto Biológico, 2012)
The objective of this work was to evaluate the effects of synthetic insecticides used in the cotton crop on eggs and third-instar larvae of the ladybeetle Cycloneda sanguinea (Linnaeus, 1763) (Coleoptera: Coccinellidae). The products used in g a.i. L-1 of water were triflumuron 0.048 (Certero 480 SC), spinosad 0.24 (Tracer 480 SC), chlorfenapyr 1.2 (Pirate 240 SC), chlothianidin 0.33 (Focus 500 WP) and imidacloprid 0.33 + β-cyfluthrin 0.042 (Connect 100 + 12.5 SC). Distilled water was used as a control. Both eggs and larvae were distributed in Petri dishes and treated with the insecticides by spraying in a Potter's tower. A fully randomized experimental design, with five replications and six treatments consisting of five pesticides and one control was used. Each plot consisted of ten eggs or third-instar larvae. The embryonic period and viability of the treated eggs; survival and duration of third-instar larvae; survival and duration of larval and pupal stages of development; sexual ratio, and the total number of eggs laid by the surviving mated females from treated eggs and third-instar larvae were evaluated. The tests were carried out at 25 ± 2º C, RH 60 ± 10% and 12h-photophase. Triflumuron 0.048 was innocuous to the predator's eggs and slightly harmful to third-instar larvae. Spinosad 0.24 was slightly harmful to eggs and third-instar larvae, whereas chlofernapyr 1.2, chlothianidin 0.33 and imidacloprid 0.33 + β-cyfluthrin 0.042 were harmful to eggs and third-instar larvae of C. Sanguinea.

Objetivou-se avaliar a seletividade fisiológica de inseticidas utilizados em algodoeiro para ovos e larvas de terceiro instar de Cycloneda sanguinea (Linnaeus, 1763) (Coleoptera: Coccinellidae). Os produtos utilizados em g i.a. L-1 de água foram triflumurom 0,048 (Certero 480 SC), espinosade 0,24 (Tracer 480 SC), clorfenapir 1,2 (Pirate 240 SC), clotianidina 0,33 (Focus 500 PM) e imidaclopride 0,33 + β-ciflutrina 0,042 (Connect 100 + 12,5 SC). Utilizou-se água destilada como tratamento testemunha. Tanto ovos quanto larvas foram distribuídos em placas de Petri e tratados com os inseticidas por meio de pulverização em torre de Potter. O delineamento experimental utilizado foi o inteiramente ao acaso, com cinco repetições e seis tratamentos constituídos pelos cinco inseticidas e pela testemunha, sendo que cada parcela foi composta por dez ovos ou dez larvas de terceiro instar. Avaliaram-se o período embrionário e a viabilidade de ovos tratados; sobrevivência e duração de larvas de terceiro instar; sobrevivência e duração dos estágios de desenvolvimento larval e pupal, razão sexual e o total de ovos colocados pelas fêmeas provenientes de ovos e larvas de terceiro instar tratados. Os bioensaios foram conduzidos a 25 ± 2º C, UR 60 ± 10% e fotofase de 12h. O inseticida triflumurom 0,048 foi seletivo a ovos do predador e levemente nocivo a larvas de terceiro instar. Espinosade 0,24 foi levemente nocivo a ovos e larvas de terceiro instar, e clorfenapir 1,2; clotianidina 0,33 e imidaclopride 0,33 + β-ciflutrina 0,042 foram prejudiciais a ovos e larvas de terceiro instar de C. Sanguinea.
Selectivity of insecticides used in the cotton crop to eggs and third-instar larvae of Cycloneda sanguinea
Keywords: Algodoeiro; coccinelídeo; predador; controle biológico; agrotóxicos; toxicidade; Cotton crop; coccinellid; predator; biological control; pesticides; toxicity